Partial synonymy of terms: Diverse labels for, and interpretations of, light verb constructions - Hrenek, Éva (Investigationes Linguisticae, 2022)
The point of departure of this paper is the hypothesis that, by examining the various labels used for the verbal expressions (also) known as light verb constructions (e.g., periphrastic constructions, pleonastic expressions, semi-compositional constructions), it is possible to pinpoint the features that the various approaches dealing with that particular category and that phenomenon interpret as definitive, essential specificities of the linguistic units in question (cf. 2.1). In addition, the exploration of the differences across categories referred to by terms that are synonymous (at least in some of their uses) might contribute to outlining the features of prototypical and non-prototypical light verb constructions, and refining the systematization of the above-mentioned expressions. In this article, I will first review the general characteristics of denomination (2.1), and those of terminology formation (2.2). After that, I will briefly sketch the approaches typically connected to the terms that are occasionally used synonymously with the term light verb construction (3). Then, on the basis of the intersection of the different approaches, I will outline a definition of light verb constructions that can currently be regarded as being the most general and accepted (4). Finally, combining several views found in the literature, I will attempt a prototype-based approach to the construction type under discussion and determine the features of prototypical light verb constructions (5).